Tinjauan Yuridis Terhadap Sanksi Tindak Pidana Dalam UUPLH Dilihat Dari Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan Pengelolaan Lingkungan Hidup - Sri Juwita Putri; Qristiana Qristiana; Nadila Khairunisa; Alief Anugrah; Herli Antoni (International Forum of Researchers and Lecturers, 2023)
In Article 80 of the Law on Environmental Protection and Management, it has been regulated regarding government coercive administrative sanctions aimed at stopping violations and taking action to restore environmental functions. According to Law no. 32 of 2009 regarding the protection and management of the environment which is already stated in Article 1 paragraph (14) which states that environmental pollution is the entry or inclusion of living things. The data analysis method used is qualitative with research results based on certain statutory norms related to environmental protection and management. In Indonesia there have been several cases that are quite detrimental and endanger the region itself. To protect the area from these things, the government also issued an Environmental Protection and Management Act aimed at protecting and preventing the environment from environmental crimes from irresponsible actors as well as informing or guiding local communities and entrepreneurs to protect their environment. Fine criminal sanctions are carried out to overcome and restore the environment, and pay compensation to the government as an environmental supervisor. The principle of ultimum remedium is applied here, namely criminal sanctions that are given after administrative sanctions have been given once to the perpetrators of crimes in the form of imprisonment and also fines. Imprisonment sanctions as an ultimatum remedium support the enforcement of norms and strengthen administrative sanctions if they are not implemented optimally.